Day-night changes in the altitude distribution, physical properties and radiative impact of low-altitude clouds over the stratocumulus-dominated subtropical oceans. (August 2017) - Gupta, Ashok Kumar; Rajeev, K.; Sijikumar, S.
Abstract: Properties of low-altitude clouds, their radiative impact and day-night changes over the subtropical oceans of prominent stratocumulus occurrence (the Northeast and the Southeast Pacific, the Southeast Atlantic, and the South Indian Ocean) are investigated using multi-year (2006–2010) CloudSat, CALIPSO and radiative flux observations. In all these regions, the occurrence, thickness and longwave radiative impact of clouds are enhanced during the nighttime, while the altitude of peak cloud occurrence (960–1200 m) remains steady. The observed features provide evidence for the physical mechanisms proposed earlier for the coupling between marine boundary layer and low-level clouds and their day-night variations over these regions. Highlights: Enhanced nighttime occurrence of low-level clouds over major subtropical oceans. Altitude of peak low-cloud occurrence (780–1280 m) increases away from coast. Lower base, higher top, larger thickness and higher LWCRF of low-clouds in night. Evidence for coupling of low-cloud properties with radiatively driven boundary layer.